PGAM5 is a key driver of mitochondrial dysfunction in experimental lung fibrosis - Ganzleben, Ingo; Prigge, Elena-Sophie (Cellular and molecular life sciences, 2019)
Mitochondrial homeostasis has recently emerged as a focal point in the pathophysiology of idiopathic pulmonary fibrosis (IPF), but conflicting data have been reported regarding its regulation. We speculated that phosphoglycerate mutase family member 5 (PGAM5), a mitochondrial protein at the intersection of multiple cell death and mitochondrial turnover pathways, might be involved in the pathogenesis of IPF.
Gesehen am 30.03.2020